Impact of Environmental Concerns on Environmental Attitudes among University Employees - Mustafa, Fatima; Zia, Saadia; Khizar, Umbreen (iRASD Journal of Economics, 2021)
The ecosystem of the world required immediate and effective actions against environmental threats. The purpose of the study was to assess the impact of environmental concerns on environmental attitudes. This is a quantitative study using a correlational design. The target population was the employees of the Institute of Southern Punjab, Multan, Pakistan. The sample size was 107 employees from the Institute of Southern Punjab, Multan, Pakistan. Instruments for collecting data were the Environmental concern scale (Diekmann & Preisendörfer, 2003) and Environmental Attitude (Dunlap, Van Liere, Mertig, & Jones, 2000). Statistical Package for Social Sciences (SPSS 23) was used to analyze data. The environmental concerns and environmental attitudes are positively correlated. Regression analysis shows a positive significant impact of environmental concerns on environmental attitudes up to 22%. There is no significant difference between genders of respondents (male, female) on environmental concerns while the significant difference is reported between genders concerning environmental attitudes. A better understanding of the beliefs and attitudes of individuals is recommended for effective eco-friendly behavior and activities.